Analysis of the Role and Responsibilities of Notaries in Storing Minutes of Deeds - Febriani, Nisrina (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Notaries have an obligation to store and maintain the minutes of the deeds they make, explained in Article 16 paragraph (1) letter b UUJN which states that Notaries have an obligation to make deeds in the form of minutes and also store them as Notary protocols. The purpose of this study is to find out, understand, study, and analyze the Notary's responsibility in his obligation to store deeds and the Legal Consequences of the Notary's responsibility in storing the minutes if there is negligence in storing them, such as damaged or lost deeds. The research method used in this study uses a normative legal approach method. The research specifications used are descriptive analytical. The types of data used consist of two data, namely primary data and secondary data consisting of primary legal materials, secondary legal materials, and secondary legal materials. The data collection method used is literature study and document study. This study uses a qualitative data analysis method. Based on the results of the study, it can be concluded that the Notary's responsibility in his obligation to store the minutes of the deed, the notary as a public official has an obligation in carrying out his position, one of which is to store the minutes of the deed. It is explained in Article 16 paragraph (1) letter b UUJN which states that notaries are required to make a deed in the form of minutes of the deed and store it as a notary protocol which is a follow-up to the provisions in Article 15 paragraph (1) UUJN. Then the legal consequences of the Notary's responsibility in storing the minutes if there is negligence in storing such as a damaged or lost deed, namely that administrative sanctions can be imposed. As stated in Article 16 paragraph (11) that the sanctions are in the form of: written warnings, temporary dismissal, honorable dismissal and dishonorable dismissal. In addition, there are not only administrative sanctions, but there are also civil sanctions and criminal sanctions.